Answer:
D. y = -1/8(x-2)² - 3
Step-by-step explanation:
General eqaution of a parabola : y = a(x-h)² + k where (h,k) is the vertex and a determines whether the parabola goes up or down as well as the width of the parabola
step 1 identify vertex
the vertex is the point that starts the curve
the vertex appears to be at (2,-3)
step 2 plug in h and k using the x and y values of the vertex
again we have y = a(x-h)² + k where (h,k) is the vertex
here the vertex is (2,-3) so h = 2 and k = -3
we get y = a(x-2)² - 3
because the curve goes down a must be negative 1/8
so the final equation would be y = -1/8(x-2)² - 3 meaning D would be the answer